Technology Acceptance of a Novel Mobile Learning Application among University Undergraduates - Hanafi, Hafizul Fahri; Zainuddin, Nur Azlan; Abd Wahab, Mohd Helmy; Ariffin, Asma Hanee (International Business Education Journal, 2018)
This paper identifies factors affecting the adoption of mobile learning application in the classroom. The principles of the Innovation Diffusion Theory (IDT) and Technology Acceptance Model (TAM) were adopted as the main elements that were investigated in this study, namely relative advantage, complexity, mobile learning acceptance, and intention to use mobile learning. The research design was based on a quantitative approach using an online survey involving a group of 200 undergraduates. Data collected were analyzed using the Comparative Fit Index (CFI) and Tucker-Lewis Index (TLI) on AMOS 20.0. Interestingly, the main research findings showed that all the indices fit the hypothesized model perfectly and all the technology acceptance constructs were significantly correlated. The finding encourage that UPSI’s undergraduates are perceptive to utilizing mobile learning approach with the utilize of novel mobile applications, which surely would have an enormous impact on the current teaching and learning practice in the campus. From the practical standpoint, such a learning paradigm would become more prevalent in many institutions of higher learning as mobile technology keeps on improving and becoming more affordable, hence enabling more students to gain unrivaled access to mobile online learning content.